Pemodelan Status Ketertinggalan Perekonomian Regional Menggunakan Geographically Weighted Logistic Regression (GWLR) - Bani Syafii, Ghulam An-Nabalah; Hanifah, Ria Dini; Arisanti, Rohimma; Pusponegoro, Novi Hidayat (Seminar Nasional Official Statistics, 2024)
The goal of economic development is to improve the well-being of the people. However, economic development, especially in developing countries, including Indonesia, has been hampered by interregional disparities. This inequality leads to a grouping of economically backward people. This research aims to find out the general picture and identify the presence of spatial aspects on the status of the regional economy backwardness and the factors that influence it from the production side. Because there are indications of dependency and spatial heterogeneity, the study uses the Geographically Weighted Logistic Regression (GWLR) model. The results show that the rise in capital and the decrease in labor will lower the tendency for one to be categorized as a backward region. Therefore, investment needs to be intensified in industries in Indonesia and it is necessary to improve the quality of technologically literate human resources to streamline the production process.